Tinjauan Yuridis atas Kebijakan Fiskal dalam Penanganan Covid-19 melalui Perppu Nomor 1 Tahun 2020 - Solihin, Solihin (Postmodernism: Indonesian Journal of Multidisciplinary Islamic Studies, 2024)
This article analyzes fiscal policy in addressing the Covid-19 pandemic through Government Regulation in Lieu of Law (Perppu) No. 1 of 2020. This Perppu was issued by the President of the Republic of Indonesia based on Article 22(1) of the 1945 Constitution during an emergency situation, such as the global Covid-19 pandemic. The pandemic had a significant impact on the national economy, leading to decreased state revenue and increased spending. The government faced the challenge of saving both public health and the economy, making fiscal policy a crucial instrument. The article also discusses the concept of freies ermessen or discretionary power, which grants the government the authority to act swiftly in emergencies to achieve public welfare. This policy prioritizes health, social safety nets, and economic recovery.